Wireless LAN radios : - Behzad, Arya (IEEE Press, 2008)
Behzad provides a high-level overview of radio design for wireless local area network (WLAN) systems. This book is intended to provide an overall understanding of the aspects of the WLAN system and the challenges present in the design of radios for the system. The author discusses both practical aspects of WLAN technology and related theory. As the popularity of WLAN continues to grow, the author notes that it is increasingly important for both system designers and circuit designers to have a thorough understanding of WLAN applications to design the next generation of radios. The book also is geared toward designers, engineers, researchers, and graduate students studying in the field.